2010
DOI: 10.3354/meps08810
|View full text |Cite
|
Sign up to set email alerts
|

Larval settlement behaviour in six gregarious ascidians in relation to adult distribution

Abstract: Settlement influences the distribution and abundance of many marine organisms, although the relative roles of abiotic and biotic factors influencing settlement are poorly understood. Species that aggregate often owe this characteristic to larval behaviour, and we investigated whether this predisposes ascidians to becoming invasive, by increasing their capacity to maintain their populations. We explored the interactive effects of larval phototaxis and geotaxis and conspecific adult extracts on settlement rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 76 publications
1
26
1
Order By: Relevance
“…Our study suggests that under low consumer pressure, mobile (and probably sessile) assemblages on floating pontoons are mainly driven by biotic habitat formation rather than by physical structure through time. This outcome echoes previous results (e.g., Rius, Branch, Griffiths, & Turon, ; Sellheim et al., ; Smith et al., ). The correlations between ecospace and MF categories appeared site‐dependent (Figure ), which may be due to different species pools and relative abundances between sites.…”
Section: Discussionsupporting
confidence: 91%
“…Our study suggests that under low consumer pressure, mobile (and probably sessile) assemblages on floating pontoons are mainly driven by biotic habitat formation rather than by physical structure through time. This outcome echoes previous results (e.g., Rius, Branch, Griffiths, & Turon, ; Sellheim et al., ; Smith et al., ). The correlations between ecospace and MF categories appeared site‐dependent (Figure ), which may be due to different species pools and relative abundances between sites.…”
Section: Discussionsupporting
confidence: 91%
“…Recruitment panels both in benthic habitats and in the water column were attached in horizontal position, because in a previous study, we observed that recruits of the ascidians C. intestinalis and P. chilensis were more abundant on the underside of artificial structures (e.g., bottom of scallop culture cages) (Dumont et al 2009). Ascidian larvae preferentially settle on shaded substratum (Miller and Etter 2008), which had also been confirmed for C. intestinalis (Rius et al 2010). Panels on rocky bottoms were attached with rigid wire cables (at 5 cm from the bottom) to mesh bags (92 9 59 cm) filled with rocks (moorings) at 4-5 m depth.…”
Section: Invasibilitymentioning
confidence: 65%
“…Many invertebrates are known to settle in response to conspecific attraction, e.g., barnacles (Dreanno et al, 2006;Elbourne and Clare, 2010;Raimondi, 1990), polychaetes (Minchinton, 1997), crabs (Donahue, 2006), and ascidians (Rius et al, 2010). D. irregulare is colonial and highly aggregated as adults, so it is possible that they settle in response to conspecific cues.…”
Section: In Situ Settlement Experiment Physical Measurements and Effmentioning
confidence: 98%